Poliploidia em Populações de Biribás (Annona Mucosa Jacq.) na Amazônia - Serbin, Giulia Melilli (Instituto Nacional Pesquisas da Amazônia - INPA, 2022)
Whole genome duplication is important in the angiosperms and cultivated plants, especially domesticated ones; however, polyploidy has been little studied in the Amazon region, where there are numerous domesticated crops. The biriba (Annona mucosa Jacq.) is a fruit tree that was domesticated by pre-Columbian populations and has polyploid populations, as well as wide phenotypic variability in fruit weight (100 g to 4 kg), as well as differences in fruit morphology. Two cytotypes are recorded in the literature (2n = 4x = 28 and 2n = 6x = 42) and genome size records are divergent (2C = 4.77, 5.42 and 6.00 pg). To decipher the role of polyploidy in the domestication of biriba, we raised questions about the phenotypic variation of the species being related to chromosome number and genome size. We performed the chromosome count of 31 individuals of biriba in central Amazonia and the middle and upper Solimões river, as well as an estimate of the DNA content with flow citometry. We performed phylogenetic reconstruction, time divergence analysis and reconstructed the ancestral chromosome number for the genus Annona. We observed that: 1) the variation in fruit size and morphotype is not associated with cytogenetic variation (chromosomal number and genome size); 2) the Rollinia group, species that belonged to the Rollinia genus such as biriba, presented a high rate of polyploids, with probability of polyploid ancestors; 3) the most recent common ancestor of Annona mucosa is inferred to be polyploid and diverged before domestication events. We conclude that when biriba was domesticated it was already polyploid and possibly natural populations already had a tetraploid genome.